Penilaian Implementasi Good Corporate Governance Pada Bumn Indonesia Sektor Perkebunan - Jeanne Asteria Wawolangi; Martinus Sony Erstiawan; Thyophoida W.S. Panjaitan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
The research was conducted at PTPN X, XI, and XII in order to see the implementation of Good Corporate Governance every PTPN. The purpose of this study is to assess the implementation of Good Corporate Governance as well as to assess the implementation of Good Corporate Governance ratings on stateowned plantation sector. Data were obtained through interviews and questionnaires. The analytical method used was a descriptive quantitative analysis. The results obtained showed that the PTPN X, XI, and XII implementation of Good Corporate Governance has been realized.